Comprehensive systematic review and meta-analysis of dyes adsorption by carbon-based adsorbent materials: Classification and analysis of last decade studies - Azari, Ali; Nabizadeh, Ramin; Nasseri, Simin; Mahvi, Amir Hossein; Mesdaghinia, Ali Reza (Chemosphere (Oxford), 2020)
Carbon-based materials and their modifications have received significant attention over the last decades given the outstanding adsorption behavior toward various dyes from aqueous solutions. In this systematic review and meta-analysis, the adsorption capability of dyes on carbon-based adsorbent materials (CBAMs) has been compiled. Further, the effects of process variables i.e., pH, adsorbent dosage, contact time, and initial concentration), adsorption kinetics, and isotherms were investigated while considering the classification of different groups of dyes and adsorbents. The Metafor package provides functions for conducting meta-analyses in R software. Electronic databases, including PubMed, Web of Science, and Scopus were systematically searched based on Medical Subject Headings (MeSH) from January 1, 2009 to May 1, 2018. The following parameters were evaluated according to predetermined inclusion and exclusion criteria. After detailed screening and analysis, 835 articles were eligible for the review section. Among them, 87 studies met all quantitative criteria for the meta-analysis. The meta-analysis was performed using a random-effects model with a high heterogeneity (I2 = 99.99%). According to the evidence, basic dyes with n = 661 (∼50%) and powder activated carbon (PAC) sorbent with n = 752 (∼57%) have received the most attention among researchers. The results revealed that the mean of removal efficiency-based dyes classification was between 79.9 and 93.7% and the adsorption capacity was lied within the range of 76.8–303.6 mg/g. Meanwhile, the maximum adsorption capacity belongs to graphene families with Qm > 320 mg/g, while the minimum Qm was related to G and GAC with capacities of 108.5 and 110.7 mg/g, respectively. Pseudo-second-order kinetic model with 88.7% and Langmuir isotherm with 74% had the best fitting with the data studied. Baujat plot revealed that two studies (ID: 75 and 12) had the minimum influence on adsorption capacity with the highest dffits and cook’s distance. According to the pooled data, the mean adsorption capacity varied between 140.90 and 208.25, with a mean of 174.57 mg/g across all studies. The results of Egger’s test (t = 0.1332, p = 0.0844) and Begg’s test (z = 0.8458, p = 0.3977) were not statistically significant, suggesting that no potential publication bias existed. •First systematic review and meta-analysis of dyes adsorption by carbon materials.•The Metafor package provides functions for conducting meta-analyses in R software.•835 articles and 78 studies were eligible for review and meta-analysis respectively.•From the pooled of data, adsorption capacity varied between 134.91 and 214.23 mg/g.•Potential publication bias did exist base Egger’s (p = 0.08) and Begg’s test (p = 0.39).